Study of Hybrid Nano Particles Flow in an Inclined Circular Artery - Syed, Waseem (Communications in Mathematics and Applications, 2026)
In the present article steady fluid flow through an inclined tube of non uniform cross section with stenosis and diltation has been investigated under the influence of hybrid nanofluid particles. Homotropy pertubation method is applied to solve the flow equations assuming mild stenosis, to determine the axial velocity, wall shear stress, pressure gradient and stream lines.Studies have examined how parameters effects on pressure gradient, impedance resistance and wall shear stress.